Liraglutide Pretreatment Does Not Improve Acute Doxorubicin-Induced Cardiotoxicity in Rats - Tonon, Carolina R. [UNESP]; Monte, Marina G. [UNESP]; Balin, Paola S. [UNESP]; Fujimori, Anderson S. S. [UNESP]; Ribeiro, Ana Paula D. [UNESP]; Ferreira, Natália F. [UNESP]; Vieira, Nayane M. [UNESP]; Cabral, Ronny P. [UNESP]; Okoshi, Marina P. [UNESP]; Okoshi, Katashi [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Minicucci, Marcos F. [UNESP]; et al. (MDPI, 2024)
Doxorubicin is an effective drug for cancer treatment; however, cardiotoxicity limits its use. Cardiotoxicity pathophysiology is multifactorial. GLP-1 analogues have been shown to reduce oxidative stress and inflammation. In this study, we evaluated the effect of pretreatment with liraglutide on doxorubicin-induced acute cardiotoxicity. A total of 60 male Wistar rats were allocated into four groups: Control (C), Doxorubicin (D), Liraglutide (L), and Doxorubicin + Liraglutide (DL). L and DL received subcutaneous injection of liraglutide 0.6 mg/kg daily, while C and D received saline for 2 weeks. Afterwards, D and DL received a single intraperitoneal injection of doxorubicin 20 mg/kg; C and L received an injection of saline. Forty-eight hours after doxorubicin administration, the rats were subjected to echocardiogram, isolated heart functional study, and euthanasia. Liraglutide-treated rats ingested significantly less food and gained less body weight than animals that did not receive the drug. Rats lost weight after doxorubicin injection. At echocardiogram and isolated heart study, doxorubicin-treated rats had systolic and diastolic function impairment. Myocardial catalase activity was statistically higher in doxorubicin-treated rats. Myocardial protein expression of tumor necrosis factor alpha (TNF-α), phosphorylated nuclear factor-κB (p-NFκB), troponin T, and B-cell lymphoma 2 (Bcl-2) was significantly lower, and the total NFκB/p-NFκB ratio and TLR-4 higher in doxorubicin-treated rats. Myocardial expression of OPA-1, MFN-2, DRP-1, and topoisomerase 2β did not differ between groups (p > 0.05). In conclusion, doxorubicin-induced cardiotoxicity is accompanied by decreased Bcl-2 and phosphorylated NFκB and increased catalase activity and TLR-4 expression. Liraglutide failed to improve acute doxorubicin-induced cardiotoxicity in rats.
Keywords: acute cardiotoxicity; doxorubicin; heart failure